Metastatic seeding of human colon cancer cell clusters expressing the hybrid epithelial/mesenchymal state. Issue 9 (1st November 2019) - Mizukoshi, Kosuke; Okazawa, Yu; Haeno, Hiroshi; Koyama, Yu; Sulidan, Kaidiliayi; Komiyama, Hiromitsu; Saeki, Harumi; Ohtsuji, Naomi; Ito, Yasuhiko; Kojima, Yutaka; Goto, Michitoshi; Habu, Sonoko; et al.
Abstract : Emerging evidence supports the theory that tumor cell clusters efficiently metastasize to distant organs. However, the roles of epithelial‐to‐mesenchymal transition (EMT) in metastasizing tumor cell clusters have not yet been fully elucidated. To investigate this issue, tumor fragments were dissected from 40 colorectal cancer (CRC) patients and implanted subcutaneously into immunodeficient mice. We observed that tumors developed from the tumor fragments obtained from 28 of the 40 CRC patients. The tumors were then dissociated into cell suspensions to be orthotopically injected into secondary mice. The tumors from 13 of the 28 patients progressed. Furthermore, metastases formed spontaneously in the liver and lungs from the tumor fragments obtained from 8 of these 13 patients. Moreover, employing a mathematical analysis, we showed that tumor cell clusters seeded these metastases significantly more often than did single tumor cells. Membrane E‐cadherin‐ and nuclear ZEB1‐positive tumor cells indicating the hybrid epithelial/mesenchymal state were also detected in primary tumors of various CRC patients, and in the corresponding patient‐derived xenografts (PDXs) and circulating tumor cell clusters in the bloodstreams of mice. In contrast, ZEB1 staining was barely detectable in the patient‐matched liver metastases presumably developing through mesenchymal‐to‐epithelial transition. Inhibition of E‐cadherin or ZEB1 expression by shRNA notably prevented the PDX‐derived tumor organoids from colonizing the liver, when injected intrasplenically into mice, indicating E‐cadherin and ZEB1 expressions to be required for their metastatic colonization. Taken together, these findings suggest that the epithelial/mesenchymal state mediates metastatic seeding of human CRC cell clusters into distant organs. Abstract : What's new? Coherent sheets of tumor cells known as tumor cell clusters exhibit a high degree of competency when colonizing distant organs during metastasis. Whether tumor cell clusters undergoing metastasis are influenced by epithelial‐to‐mesenchymal transition, however, remains unknown. Here, in patient‐derived tumor xenograft murine models of colorectal cancer (CRC), hybrid epithelial/mesenchymal plasticity in tumor cell clusters was found to drive metastatic seeding. Human CRC cell clusters seeded spontaneous metastases more often than single tumor cells. In addition, E‐cad‐ and ZEB1‐expressing hybrid tumor cells were detectable in CRC cell clusters. Inhibition of these factors attenuated liver metastasis in mice following intrasplenic CRC cell organoid injection.